2022
DOI: 10.1097/ypg.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Emotional dysregulation, alexithymia and neuroticism: a systematic review on the genetic basis of a subset of psychological traits

Abstract: Neuroticism, alexithymia and emotion dysregulation are key traits and known risk factors for several psychiatric conditions. In this systematic review, the aim is to evaluate the genetic contribution to these psychological phenotypes. A systematic review of articles found in PubMed was conducted. Search terms included ‘genetic’, ‘GWAS’, ‘neuroticism’, ‘alexithymia’ and ‘emotion dysregulation’. Risk of bias was assessed utilizing the STREGA checklist. Two hundred two papers were selected from existing literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 298 publications
0
1
0
Order By: Relevance
“…Resaerchers have also found that COMT is associated with emotional dysregulation and that dopamine receptor 2 genes can be a promising target of antipsychotic medications [e.g., 331 ]. Additionally, for monoamine oxidase A, H allele carriers have greater stress effects on the right anterior hippocampus hypoactivity and cortisol hyperresponse as compared to the L allele carriers [ 332 ].…”
Section: Effects Of Stress On Neuronal Mechanisms Shared With Cogniti...mentioning
confidence: 99%
“…Resaerchers have also found that COMT is associated with emotional dysregulation and that dopamine receptor 2 genes can be a promising target of antipsychotic medications [e.g., 331 ]. Additionally, for monoamine oxidase A, H allele carriers have greater stress effects on the right anterior hippocampus hypoactivity and cortisol hyperresponse as compared to the L allele carriers [ 332 ].…”
Section: Effects Of Stress On Neuronal Mechanisms Shared With Cogniti...mentioning
confidence: 99%